Ocena zawartości metali ciężkich w glebach i wybranych roślinach w rejonie oddziaływania Zakładów Chemicznych "Wizów" S.A. = Contents assessment of heavy metals in soils and chosen plants in area effects of Chemical Company Wizów S.A. - Kamińska, Anna Jolanta; Kulczycki, Grzegorz; Spiak, Zofia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article was presented influence one of the biggest producer of polyphosphate in Poland on the floras and soils environment. Except the most toxic relationships of sulphur and fluor, to the atmosphere are emitted the heavy metals as well. In the sample tests were qualified content soluble forms of metals in the soils in dependence from distances of source emission and direction of winds and content the same metals in various plants. Quantity of these elements was very varied both in soils and in plants (in the most of cases it did not cross limited values).Was observed various concentration of tests metals in dependence from this, where samples were taken.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); metale ciężkie; gleba; roślinność; zakłady chemiczne; heavy metals; soils; plants; chemical company